Efficient Intramolecular C–H Insertion Catalyzed by Iridium Porphyrin Complexes - López-Sánchez, Cristóbal; Álvarez-Corral, Míriam; Muñoz-Dorado, Manuel; Rodríguez-García, Ignacio (Synlett, 2012)
Octaethylporphyrin and tetraphenylporphyrin Ir(I) and Ir(III) complexes are useful catalysts for intramolecular C–H insertion processes of stabilized diazo compounds. While the Ir(I) complex TPP[Ir(CO)3]2 is the most efficient and selective catalyst, the others afford mixtures of cyclization and dimerization products. The effect of the solvent polarity on the selectivity of the reaction is also presented.
Keywords: iridium complexes; porphyrins; diazo compounds; carbene complexes; intramolecular C–H insertion